ATRT-35. SMARCB1-DEFICIENT TUMORS ACTIVATE BOTH INNATE AND ADAPTIVE IMMUNE RESPONSES AND ARE SUSCEPTIBLE TO CHECKPOINT BLOCKADE AND TLR3 ACTIVATION. Issue 2 (22nd June 2018) - Leruste, Amaury; Caudana, Pamela; Tauziede-Espariat, Arnault; Han, Zhi-Yan; Ramos, Rodrigo N; Nikolic, Jovan; Tosello, Jimena; Brohard, Solene; Andrianteranagna, Mamy; Chauvin, Céline; Masliah-Planchon, Julien; Sedlick, Christine; et al.
Abstract: In order to evaluate the immune infiltrate of AT/RT, we conducted a combined immunohistochemical, multiparametric flow cytometry and transcriptomic analysis of a series of 49 human AT/RT. This revealed substantial heterogeneity, with some subgroups of AT/RT showing a prominent immune infiltrate. In details, our analyses indicated that: i) myeloid cells were the most abundant immune population, including both microglial cells and non-resident pro-tumoral M2-polarized macrophages, ii) tumor-infiltrating lymphocytes consisted in equal proportions of CD4+ and CD8+ T cells with few regulatory T cells, and iii) immune modulatory molecules PD-L1 and TIM-3 were expressed at high levels. Intratumoral cytolytic activity of CD8+ T cells highly correlated with both interferon gamma and alpha signatures, confirming the involvement of both adaptive and innate immune cells in the anti-tumor response. A genetically engineered mouse model of AT/RT recently established in our laboratory recapitulates many of these traits, including important infiltration by both lymphoid and myeloid cells sharing similar phenotypic characteristics. Using this model, we showed that blockade of the PD-1/PD-L1 pathway significantly impaired tumor growth and induced memory against a second engraftment, confirming an anti-tumoral T cell memory response. Combination with TIM-3 blockade showed synergistic effects. Additionally, targeting the myeloid infiltrate by TLR3 activation with poly(I:C) induced a potent anti-tumor effect which, combined with PD-1 blockade, led to complete tumor regression in over 85% of treated mice. In conclusion, we demonstrate that immune infiltration is a recurrent property of AT/RT and that immunotherapy, particularly combination regimens, have promising therapeutic potential.